Photocapture of dynamic hydrogen-bonded assemblies - Nathan D. McClenaghan; Dario M. Bassani (International Journal of Photoenergy)
Recent advances in the continuing study of [2+2] photodimerization reactions in supramolecular, non-covalent systems are presented. The covalent photocapture of small dynamic assemblies which are formed using weak hydrogen-bonding interactions between two different complementary units, barbiturates and melamines, is discussed. One unit serves as a photo-inert supramolecular template capable of bringing two photoactive units together using multiple hydrogen-bonds. The second type of unit unites the corresponding, complementary hydrogen-bonding motif with a photoactive unit. Irradiation of the supramolecular assemblies leads to photodimerization of adjacent units and generation of an imprinted site for the template. Moieties which are adapted to participate in photodimerization reactions are styrene, cinnamate, stilbene and fullerene units. The results are interpreted on the basis of topochemical reaction control.